Analyzing the food supply chain : asking questions, evaluating evidence, and designing solutions - Steele, Philip, 1948- (Steele, Philip, 1948- Analyzing environmental change., 2019)
Briefly explores the history and origins of concerns about the ethics and limitations of the world's modern food supply chain, and surveys the important questions being asked, how to evaluate the evidence, and how people think about and are coming up with solutions. Includes a glossary.